(untitled) (Issues in Social and Environmental Accounting (ISEA), 2014)
The objectives of this study is to investigate the association between CSR and Corporate Fi nancial Performance (CFP). This study investigates 800 firms listed on Indonesian Stock Ex change in 2010 - 2012. Financial performance is measured by accounting-based approach and stock-market-based approach. While, CSR practices is measured by Corporate Social Disclo sure Index (CSRDI). Thus, the association was analyzed under multivariate linear regression by considering time difference. Firm size, growth, and risk are included as control variables. This study finds: (1) CSR provides positive impact on the financial performance until one next period; (2) financial performance measured by ROA influence positively CSR only the next two years; (3) there is significant positive relationship between firm size and CSR. The paper has implications in enhancing the understanding of company performance through understand ing the association between CSR and CFP.This may increase the understanding of the associa tion between CSR and CFP. The findings of this study contribute to the literature and regulator on CSR.